HAMBATAN BIROKRASI DALAM MELAKSANAKAN TUGAS (STUDI PATOLOGI BIROKRASI PADA PEGAWAI KANTOR CAMAT TALO KECIL KABUPATEN SELUMA) - Rijono, Rijono (Jurnal Governance dan Administrasi Publik, 2020)
This study aims to determine the pathology of bureaucracy in the employees of the Head Office of the Talo Kecil Seluma sub-district seen from the perceptions and managerial style of the apparatus in the bureaucracy, the knowledge and skills of the apparatus implementing various operational activities, the actions of bureaucratic members who violate legal norms, prevailing laws and regulations, dysfunctional bureaucratic behavior and views of the internal situation in various analyzes in environmental governance. An interesting phenomenon to be observed and raised to the surface is that there are still practices of abuse of authority and responsibility at the level of the managerial bureaucracy so that indications of a new paradigm of governance and government ethics in public assessments are not in accordance with the mandate of reform. As a result, there was a problem of not following up on writing letters from employees to their subordinates. In addition to prioritizing serving civil servants to their families, the knowledge and skills of employees are still low, it can be seen that there are still employees who take high school education / equivalent, the head of employees is also less able to operate computers, in carrying out work there are levies made by employees to the community in making family cards, birth certificates and ID cards, there is no cupboard for storing archives so they are placed on the floor near the table, making community cover letters have to wait a long time, employees are often indifferent in serving the community, neglect their duties because they are late arriving and do not attend morning apples because before going to the office employees first go to the garden to tap rubber and during breaks the employees return home for lunch with various reasons and also employees of the Talo Kecil Seluma sub-district head office are not aware of the problems that occur in their work areas such as floods and lack of transportation. motivation to serve the community as much as possible.